2002
DOI: 10.1002/lsm.10123
|View full text |Cite
|
Sign up to set email alerts
|

Tissue welding with biodegradable polymer films–demonstration of acute strength reinforcement in vivo

Abstract: Polymer film patches may be a viable method to increase acute breaking strengths of welds using topically applied solder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
0
18
1
Order By: Relevance
“…The film placement in this particular study is different from previous studies [18][19][20]. There are two reasons for the change in film placement for this study.…”
Section: Introductioncontrasting
confidence: 43%
See 2 more Smart Citations
“…The film placement in this particular study is different from previous studies [18][19][20]. There are two reasons for the change in film placement for this study.…”
Section: Introductioncontrasting
confidence: 43%
“…The laser spot was manually scanned back and forth over the incision at a speed of about 1 cm/second for a total irradiation time of 50 seconds. The laser irradiance used was based on irradiances that yielded satisfactory weld strengths in previous in vitro studies [18][19][20] for a different welding geometry (topical application of the solder). A small set of trial experiments was performed to test the laser parameters and welding technique before conducting the experiments in this study (data not shown).…”
Section: Laser-soldering Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biodegradable polymers such as polyglycolic acid or polycaprolactone have been used as carrier material for the liquid solder. They prevent runaway of the liquid solder and give additional strength to the anastomosis [13,[18][19][20][21].…”
Section: Biophotonicsmentioning
confidence: 98%
“…Effective results using chromophore-doped solders have been reported for various tissues as arteries and skin. Another improvement of traditional protein solders relies on the addition to the albumin solution of biopolymers, such as PLGA (poly(DL-lactic-co-glycolic acid)), which act as porous scaffolds [13]. These provide better flexibility as well as improved repair strength over albumin solders alone.…”
mentioning
confidence: 99%